Respective roles of non-pharmaceutical interventions in bronchiolitis outbreaks: an interrupted time-series analysis based on a multinational surveillance system. Issue 2 (16th February 2023) - Lenglart, Lea; Ouldali, Naim; Honeyford, Kate; Bognar, Zsolt; Bressan, Silvia; Buonsenso, Danilo; Da Dalt, Liviana; De, Tisham; Farrugia, Ruth; Maconochie, Ian K.; Moll, Henriette A.; Oostenbrink, Rianne; et al.
Background: Bronchiolitis is a major source of morbimortality among young children worldwide. Non-pharmaceutical interventions (NPIs) implemented to reduce the spread of severe acute respiratory syndrome coronavirus 2 may have had an important impact on bronchiolitis outbreaks, as well as major societal consequences. Discriminating between their respective impacts would help define optimal public health strategies against bronchiolitis. We aimed to assess the respective impact of each NPI on bronchiolitis outbreaks in 14 European countries. Methods: We conducted a quasi-experimental interrupted time-series analysis based on a multicentre international study. All children diagnosed with bronchiolitis presenting to the paediatric emergency department of one of 27 centres from January 2018 to March 2021 were included. We assessed the association between each NPI and change in the bronchiolitis trend over time by seasonally adjusted multivariable quasi-Poisson regression modelling. Results: In total, 42 916 children were included. We observed an overall cumulative 78% (95% CI −100– −54%; p<0.0001) reduction in bronchiolitis cases following NPI implementation. The decrease varied between countries from −97% (95% CI −100– −47%; p=0.0005) to −36% (95% CI −79–7%; p=0.105). Full lockdown (incidence rate ratio (IRR) 0.21 (95% CI 0.14–0.30); p<0.001), secondary school closure (IRR 0.33 (95% CI 0.20–0.52); p<0.0001), wearing a mask indoors (IRR 0.49 (95% CI 0.25–0.94); p=0.034) and teleworking (IRR 0.55 (95% CI 0.31–0.97); p=0.038) were independently associated with reducing bronchiolitis. Conclusions: Several NPIs were associated with a reduction of bronchiolitis outbreaks, including full lockdown, school closure, teleworking and facial masking. Some of these public health interventions may be considered to further reduce the global burden of bronchiolitis. Among the various non-pharmaceutical interventions implemented against SARS-CoV-2 in Europe, full lockdown, school closure, facial masking and teleworking were preventive measures associated with a reduction in the number of bronchiolitis cases https://bit.ly/3SyqqYS